Diagnóstico fisicoquímico y microbiológico del queso fresco no pasteurizado comercializado en la parroquia Membrillo del cantón Bolívar - Valencia Ganchozo, Vicky Xiomara (2025)
The objective of the present research was to evaluate the physicochemical and microbiological quality of fresh cheeses sold in Membrillo parish, Bolívar canton, Manabí. A study was conducted in 10 shops selling unpasteurized fresh cheese. A structured observation checklist was used, based on the NTE INEN 2687-04(2013) standard for healthy markets. The aim was to identify possible sources of cheese contamination. One sample of fresh cheese was taken from each establishment and subjected to physicochemical (fat, moisture) and microbiological analyses (Escherichia coli, Staphylococcus aureus, Salmonella spp.). The results revealed a low level of compliance in the 10 establishments regarding control points such as cleanliness, location, and hygiene practices in the sales and refrigeration areas. Physicochemically, the cheese samples did not meet the minimum fat content (45%) required by the NTE INEN 1528:2012 standard; however, the moisture levels were within the permitted limits. High counts of Escherichia coli and Staphylococcus aureus were found, exceeding the limits established by the standard, although Salmonella spp. was not detected, thus complying with the regulation in that aspect. A guideline was developed for cheese producers and vendors in Membrillo parish, based on the ARCSA (2015) standard, to improve their cheese production practices.